2006
DOI: 10.1111/j.1530-0277.2006.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Attenuates Load‐related Activation During a Working Memory Task: Relation to Level of Response to Alcohol

Abstract: Background-A low level of response to alcohol is a major risk factor for the development of alcohol dependence, but neural correlates of this marker are unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
49
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 60 publications
7
49
1
1
Order By: Relevance
“…Using PET imaging with alcoholics and cocaine patients, research has shown a significant association between dopamine D2 receptor binding in the VS and drug craving as well as motivation for self-administration Martinez et al 2005Martinez et al , 2007. On the other hand, neuropsychological and imaging studies examining prefrontal executive functions, including impulse control, decision making and set shifting, have shown executive function deficits and hypo-frontal responses in addicted individuals compared to control volunteers (Ersche et al 2005(Ersche et al , 2006(Ersche et al , 2008Hester and Garavan 2004;Kaufman et al 2003;Li and Sinha 2008;Noel et al 2007;Paulus et al 2006). Together, these data show a distinct pattern of findings indicating that increased stress-and cueinduced craving and compulsive drug-seeking states in addicted individuals are associated with greater activity in the striatum, but decreased activity in specific regions of the cingulate and prefrontal cortex and related regions involved in controlling impulses and emotions (Li and Sinha 2008).…”
Section: Neural Correlates Of Stress and Drug Craving In Addictionmentioning
confidence: 99%
“…Using PET imaging with alcoholics and cocaine patients, research has shown a significant association between dopamine D2 receptor binding in the VS and drug craving as well as motivation for self-administration Martinez et al 2005Martinez et al , 2007. On the other hand, neuropsychological and imaging studies examining prefrontal executive functions, including impulse control, decision making and set shifting, have shown executive function deficits and hypo-frontal responses in addicted individuals compared to control volunteers (Ersche et al 2005(Ersche et al , 2006(Ersche et al , 2008Hester and Garavan 2004;Kaufman et al 2003;Li and Sinha 2008;Noel et al 2007;Paulus et al 2006). Together, these data show a distinct pattern of findings indicating that increased stress-and cueinduced craving and compulsive drug-seeking states in addicted individuals are associated with greater activity in the striatum, but decreased activity in specific regions of the cingulate and prefrontal cortex and related regions involved in controlling impulses and emotions (Li and Sinha 2008).…”
Section: Neural Correlates Of Stress and Drug Craving In Addictionmentioning
confidence: 99%
“…All participants were administered the same VWM task (Paulus et al, 2006;Tapert et al, 2004a) during fMRI acquisition. Each trial consisted of an array of 2, 4, or 6 colored dots briefl y (100 ms) presented against a gray background.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies of alcohol and attention have shown the alcohol impairs performance on divided-attention tasks (e.g., Lex et al, 1996;Maylor et al, 1990;Leigh et al, 1977;Fisk & Scerbo, 1987;Moskowitz & DePry, 1968) but has less consistent effects on concentrated attention tasks (Koelega, 1995). Therefore, we expect that most WM measures using a dual-task procedure, like the visual-spatial WM task used by Schweizer et al (2006), would be more sensitive to the effects of alcohol than a focusedattention task, like the array tasks used in the present experiment and the visual-spatial WM task used by Paulus et al (2006), that do not benefit from rehearsal, or the immediate verbal WM task that Schweizer et al (2006) combined with rehearsal-blocking activity. On the other hand, we still expect alcohol to affect certain focused attention tasks that profit from rehearsal and grouping, like the sequential tasks in our experiment and the backward digit span used by Finn et al (1999).…”
mentioning
confidence: 95%
“…Schweizer et al did find that alcohol impaired performance on a visual-spatial WM task (testing memory of three locations after a 30-s visual-spatial distraction task) during declining BAC (from 0.09 to 0.08), suggesting that alcohol effects on WM may be modality specific. However, Paulus, Tapert, Pulido, and Schuckit (2006) used a different visual-spatial WM task than Schweizer et al (a visual array comparison task after Luck and Vogel, 1997) and found no significant effect of alcohol (at a mean BAC of 0.06). Similarly, Weissenborn and Duka (2003) failed to find that alcohol impaired spatial working memory (remembering search locations in a self-ordered search task) or pattern recognition (recognizing patterns from a previous sequence of 12 patterns), but did find that it impaired planning (in a Tower of London test) and spatial recognition (recognizing locations from a previous sequence of 5 locations).…”
mentioning
confidence: 99%